Sedimentation Analysis Based on Land Use Change on Service Life Estimation in the Gerokgak Reservoir Buleleng Regency - Putra, I Wyn Ari Yoga Pratama; Arsana, I Gusti Ngurah Kerta; Pariartha, I.P. Gustave Suryantara (Universitas Ibn Khaldun Bogor, 2025)
A common problem faced by most reservoirs during their operational period is sedimentation. Sedimentation problems occur due to high levels of land erosion which is influenced by land use in the reservoir catchment area. Based on this, the aim of this research is to determine changes in land use in the reservoir catchment area, the amount of erosion and sedimentation caused by land use and the influence of erosion on the estimated service life of the reservoir. The research location is in the water catchment area of ​​the Gerokgak Reservoir, Buleleng Regency, Bali Province. The data needed in this research includes land use maps and topography of the reservoir catchment area, planning data for the Gerokgak Dam and soil types. The methods used in this research are the Universal Soil Loss Equation (USLE) method to predict the amount of land erosion and the Sediment Delivery Ratio to determine the percentage of sediment entering the reservoir as well as the dead storage comparison method with the amount of sediment to determine the estimated service life of the reservoir. Based on the land use map, the land use condition of the Gerokgak Reservoir water catchment area in 2023 is 95.5% forest and 4.5% rice fields. The average rate of land erosion from 2018 to 2023 is 27.427 tons/ha/year with potential sedimentation of 9,698.563 tons/year. Based on the amount of sediment, it can be analyzed that the service life of the Gerokgak Reservoir is around 5.279 years.